POTENSI UMKM BERBASIS EKONOMI KREATIF DAN PARIWISATA SEBAGAI SEKTOR UNGGULAN DAERAH: Hari Susanta Nugraha, Rabith Jihan Amaruli, dan Darwanto - Dialektika Publik (Dialektika Publik, 2017)
Unit Micro, Small and Medium Enterprises (MSME) is a business unit that provides a positive impact on the economy and the artery of the regional and national economy. MSMEs products was considered to serve as a flagship product in international trade. However, there are still some MSMEs’s products such as products of creative MSME and tourism that needs to be given special attention related to product development of MSME. The purpose of this study was to analyze the potential uniqueness, local knowledge and institutions in the development of MSME products based creative economy and tourism. The analytical method used is a qualitative descriptive analysis method using Strength, Weakness, Opportunities, and Threats (SWOT) analysis based on data derived from the results of in-depth interview with key person who manage the tourism destination. The results show that the identification of strengths, weakness, opportunities and threats MSME products based creative economy and tourism so that it can be used as a reference in formulating strategies and models of strengthening the MSMEs products that require an active role of government and local communities to participate in the development of MSMEs based creative economy and tourism and the role of institutions is one of the most important things in the development of MSMEs based creative economy and tourism.